Synthesis and properties of semiconductor bismuth sulfide iodide for photoelectrochemical applications - Xeniya Alexandrovna Leontyeva; Darya Sergeevna Puzikova; Margarita Borisovna Dergacheva; Gulinur Marsovna Khussurova; Polina Vyacheslavovna Panchenko (Journal of Saudi Chemical Society)
This review article provides an overview of the properties and methods for synthesis of BiSI and Bi13S18I2 semiconductor compounds in the form of thin films, powders and crystals, as well as their application in photovoltaic and photoelectrochemical devices. Over the past decade, the results of extensive and versatile research on the structure, properties, functionality and potential applications of bismuth-containing semiconductor materials have accumulated. Bismuth halides and chalcohalides are a developing class of materials that have a small band gap, high chemical stability, effective absorbing properties when absorbing light radiation, which causes the registration of high quantum efficiency values and the possibility of their use in photoelectrochemical processes and photovoltaic solid-state elements. This review presents the results of recent developments and basic approaches aimed at obtaining various multicomponent compounds based on bismuth and improving photoelectrochemical properties. Various structures which demonstrate the importance of thin films based on bismuth compounds are also described. The key problems related to the synthesis and development of these materials is presented. This review will provide a deeper understanding and determine the preferred direction for the synthesis of bismuth-containing thin films for energy and environmental applications.